Synthesis of a biocompatible poly(2-hydroxyethyl methacrylate)-chitosan core-shell hydrogel latex - Somkieath Jenjob (2018)
Core-shell hydrogel latexes, composed of a poly(2-hydroxyethyl methacrylate) (PHEMA) core chemically coated with chitosan (CS) shell, were synthesized via an emulsifier-free emulsion polymerization, free radically initiated by a redox couple of tert-butyl hydroperoxide and amine groups on CS itself. The variation of some polymerization parameters [e.g., polymerization time, CS/2-hydroxyethyl methacrylate (HEMA) weight ratio, and content of crosslinker] was systematically investigated in this study. We found that the weight ratios between CS and the HEMA monomer influenced the course of polymerization, which was traced by the change in percentage monomer conversions, and the colloidal stability of the PHEMA-CS hydrogel latexes obtained. Moreover, the polymerization time affected their particle sizes and surface charges. For the colloidally stable PHEMA-CS hydrogel latexes, their sizes and charges ranged from 600 to 689 nm and from 32 to 51 mV, respectively. N,N-Methylene bisacrylamide was used as a crosslinking agent for the core component; this was found to be able to enhance the hydrogels' thermal stability and water uptake. Moreover, the 3-[4,5-dimethylthiazol-2-yl]-2,5- diphenyltetrazolium bromide assay showed that 100% cell viability was achieved during the treatment of the PHEMA-CS latex (0.2-2.5 mg/mL) with Caco-2 cells. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2014, 131, 40003. Copyright © 2013 Wiley Periodicals, Inc.